Synthesis of ultra-thin carbon layers on SiC substrate by ion implantation. (November 2015) - Wang, Xu; Zhang, Yanwen; Tang, Meixiong; Han, Dong; Fu, Engang; Xue, Jianming; Zhao, Ziqiang
Abstract: Direct synthesis of uniform thickness and large-size monolayer or multilayer graphene films on insulating/semiconducting substrates are desirable for future nanoelectronics. In this work, ion implantation technique is used to produce ultra-thin carbon layers directly on the (0 0 0 1) Si-face of a 6H-silicon carbide surface. C ions are implanted in Si-face of SiC followed by thermal annealing. Upon cooling, C atoms, either implanted or supplied by the substrate, segregate to the surface and self-assemble into thin carbon layers. Compared with by thermal decomposition to grow epitaxial graphene on SiC, the ion implantation-annealing method requires much lower graphitization temperature. To understand the growth mechanism, a characterization of our thin carbon layers has been performed using comprehensive structural and chemical analyses. This synthesis method is promising for industrial production, deserving considerable attention in the future.